Nonlinear resonant jump in rudder positioning elecrohydraulic systems - Horvat, Krunoslav; Koroman, Vladimir; Kuljača, Ognjen (2008)
Summary: The rudder positioning electrohydraulic system, as many other complex systems, is a nonlinear system. In nonlinear systems, a nonlinear resonant jump can occur. The paper deals with the analysis of the rudder positioning electrohydraulic system regarding the nonlinear resonant jump caused by saturation of the electrohydraulic proportional valve. The meaning of the term “resonant jump” is explained in the introduction. Then, the basics needs for occurrence of nonlinear resonant jump phenomenon are given. The rudder positioning electrohydraulic system is also described. Two methods of analyzing system with respect to resonant jumps are described: the analytical method and the simulation method. When performing the analytical analysis based on the describing function approach, the analysis of the variations of important parameters, including saturation, is performed. Then, the confi rmation of the results of analytical analysis is illustrated by the simulation method. Also, the simulation procedures, like creating an excitation signal and accelerating the simulation by using vectors in Simulink/Matlab simulation software package, are explained in detail
Bibliografija: 11 jed
Sažetak
Keywords: Brodsko kormilo; Brodski strojni sustavi -- Automatizacija -- Simulacijski modeli